2016
DOI: 10.1186/s12891-016-1189-2
|View full text |Cite
|
Sign up to set email alerts
|

Are online symptoms checkers useful for patients with inflammatory arthritis?

Abstract: BackgroundOnline symptom checkers are increasingly used by patients however there is little published evidence of their effectiveness in real patients. The aim of this study was to evaluate how patients with inflammatory arthritis and inflammatory arthralgia use the internet to look for health information and to assess the advice given and diagnoses suggested by the NHS and WebMD symptom checkers in relation to the patients’ actual diagnoses.MethodsThirty-four patients with inflammatory arthritis (rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 11 publications
2
79
0
3
Order By: Relevance
“…As reported in previous studies [ 25 , 28 ], our work clearly shows that most patients regularly use the internet to retrieve medical information. In a previous study [ 3 ] published in 2016, 47% of the patients consulted the internet to investigate their symptoms. This proportion seems to be increasing, as in our study 67% and in another recent study [ 25 ] 95% of patients stated they did so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in previous studies [ 25 , 28 ], our work clearly shows that most patients regularly use the internet to retrieve medical information. In a previous study [ 3 ] published in 2016, 47% of the patients consulted the internet to investigate their symptoms. This proportion seems to be increasing, as in our study 67% and in another recent study [ 25 ] 95% of patients stated they did so.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, mHealth solutions, such as mobile apps and wearable sensors could empower patients, provide individual support, and lead to better outcomes than those available through standard care. Patients with chronic rheumatic diseases already have access to a broad range of mHealth solutions, starting from symptom checkers [ 3 ] or referral tools [ 4 ]. Once a diagnosis is established, mHealth tools enable patients to better monitor their symptoms passively through sensors [ 5 ] and actively by entering data [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The internet is an important source of information for both health care professionals and members of the public. Patients often check their symptoms online prior to seeing a rheumatologist [ 21 ]. Symptom checkers represent a professional alternative to search engines.…”
Section: The Value Of Current Symptom Checkers In Rheumatologymentioning
confidence: 99%
“…The use of symptom checkers in rheumatology has been explored only on a minor level. Powley et al [ 21 ] recently evaluated two freely available symptom checkers which included a broad variety of different diseases, and were thus not rheumatology-specific. The study showed that the help-seeking advice and diagnoses given by the symptom checkers tested was frequently inaccurate for rheumatic diseases, correctly identifying inflammatory arthritis in only 4 of 21 (19%) patients.…”
Section: The Value Of Current Symptom Checkers In Rheumatologymentioning
confidence: 99%
“…The approach adopted in other vignettes studies by [3,6,[20][21][22][23][24] has been to determine the percentage of all vignettes for which the app (or tested-GP) provided an appropriate conditionsuggestion -here this analysis method is referred to as the 'required-answer' approach. Results are shown in Fig.…”
Section: Suggested Conditions: the 'Required-answer' Approachmentioning
confidence: 99%